Microfluidic Technology for the Isolation and Analysis of Exosomes - Wu, Yusong; Wang, Yuqing; Lu, Yanjun; Luo, Xiaomei; Huang, Yinghong; Xie, Ting; Pilarsky, Christian; Dang, Yuanye; Zhang, Jianye (Micromachines, 2022)
Exosomes are lipid-bilayer enclosed vesicles with diameters of 30–150 nm, which play a pivotal role in cell communication by transporting their cargoes such as proteins, lipids, and genetic materials. In recent years, exosomes have been under intense investigation, as they show great promise in numerous areas, especially as bio-markers in liquid biopsies. However, due to the high heterogeneity and the nano size of exosomes, the separation of exosomes is not easy. This review will deliver an outline of the conventional methods and the microfluidic-based technologies for exosome separation. Particular attention is devoted to microfluidic devices, highlighting the efficiency of exosome isolation by these methods. Additionally, this review will introduce advances made in the integrated microfluidics technologies that enable the separation and analysis of exosomes.
CRIS-Team Scopus Importer:2022-11-11
Keywords: detection; exosomes; extra-cellular vesicle; isolation; microfluidics